2012
DOI: 10.1159/000336107
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease and End-Stage Renal Disease Predict Higher Risk of Mortality in Patients with Primary Upper Gastrointestinal Bleeding

Abstract: Background: The outcome of gastrointestinal bleeding in chronic kidney disease (CKD) and end-stage renal disease (ESRD) patients is difficult to discern from the literature. Many publications are small, single-center series or are from an era prior to advanced interventional endoscopy, widespread use of proton pump inhibitors or treatment for Helicobacter pylori infections. In this study, we quantify the role of CKD and ESRD as independent predictors of mortality in patients admitted to the hospital with a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 23 publications
3
48
0
1
Order By: Relevance
“…The association between lower serum albumin values and higher UGIB risk is also supported by a previous study in patients with CKD receiving dialysis (19). A history of UGIB is an important risk factor but has not been taken into consideration in previous studies (1)(2)(3)6,(20)(21)(22). Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The association between lower serum albumin values and higher UGIB risk is also supported by a previous study in patients with CKD receiving dialysis (19). A history of UGIB is an important risk factor but has not been taken into consideration in previous studies (1)(2)(3)6,(20)(21)(22). Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB.…”
Section: Discussionsupporting
confidence: 85%
“…In patients with CKD, UGIB-related hospitalization is associated with a 3-fold increase in in-hospital mortality (2). Risk factors of UGIB include diabetes mellitus, coronary artery disease (CAD) (3), cirrhosis (4,5), use of nonsteroidal anti-inflammatory drugs (NSAIDs) (5), and history of UGIB in patients with CKD (6).…”
Section: Introductionmentioning
confidence: 99%
“…Higher risk of gastrointestinal bleeding and subdural hematomas in this population have been described previously. 21,22 Defects in coagulation pathway and use of anticoagulation in dialysis are thought to contribute toward this increased risk of bleeding in patients on maintenance dialysis. We found the incidence of SAH hospitalizations to be higher in females and blacks irrespective of need for maintenance dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…This conferred with the findings from a large observational study. 7 Uremia was long thought as one of the most important reasons for bleeding in renal disease patients. 21,22 However, even with adjustment of uremia in our study population ESRD continued to have a higher degree of recurrent GIB.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similarly, patients with chronic kidney disease and ESRD are at higher risk of developing upper gastrointestinal bleeding that increases the mortality by 3 folds in these patients. 7 Atrial fibrillation patients who are anticoagulated are also at 3 folds higher risk of gastrointestinal bleeding. 8 There is currently no data available about the chronic kidney disease or ESRD patients who develop gastrointestinal hemorrhage and interrupt anticoagulation.…”
Section: Introductionmentioning
confidence: 99%